THE IMPLEMENTATION OF STUDENT TEAM ACHIEVEMENT DIVION AND PICTURE SERIES ON IMPROVING THE SPEAKING SKILL OF THE 3RD GRADE STUDENTS OF CIPTA DHARMA ELEMENTARY SCHOOL IN ACADEMIC YEAR 2016/2017 - Handayani, Nengah Dwi; Kumara, Dewa Gede Agung Gana (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2017)
Speaking is one of language skills that should be improved by students. In order to improve the skill, teacher should be carefull in choosing techniques and media used for teaching. The aim of this research was to find out whether or not the Speaking Skill of the 3rd grade students of Cipta Dharma Elementary School could be improved through Student Team Achievement Division (STAD) and Picture Series in Academic Year 2016/2017. This Research used a Classroom Action Research with the total 36 students taken as subject. The result was, in Pre Cycle52.78% (19 students); in Cycle 1 69.44% (25 students); and in Cycle 2 88.89% (32 students) reached the minimum completeness learning mastery. Based on the result, it could be concluded that the subject?s Speaking Skill could be improved the implementation of STAD and Picture Series.